EFFECT OF SERVICE QUALITY, PRICE AND LOCATION ON CUSTOMER SATISFACTION (Study on PT AHASS SIAP Motor Bandung) - Fitri Julianti; Yoyo Sudaryo; Mochammad Mukti Ali; Andre Suryaningprang; Erna Herlinawati; Dadan Abdul Aziz (Sean Institute, 2023)
This study aims to determine the effect of service quality, price and location on customer satisfaction. The object of this study is the consumer of PT AHASS SIAP Motor Bandung. This study was conducted on 73 respondents using a quantitative approach. Data analysis used is regression analysis that is processed with the application of SPSS 26. The results of this study showed that the description of service quality variables (X1), price (X2), location (X3) and purchase decision (Y) are very good categories. Then in the T test (partial) there is a significant influence between the quality of Service (X1) to customer satisfaction (Y), price (X2) to customer satisfaction (Y), and location (X3) to customer satisfaction. likewise, the test f (simultaneous) both independent variables, service quality (X1), price (X2) and location simultaneously affect the dependent variable customer satisfaction (Y). then, from the value of the coefficient of determination, shows customer satisfaction (Y) 91.4% influenced by service quality (X1), price (X2) and location (X3). Meanwhile, 8.6% were explained by variables outside the study.